1996
DOI: 10.1530/eje.0.1340751
|View full text |Cite
|
Sign up to set email alerts
|

Developmental aspects of prolactin receptor gene expression in fetal and neonatal mice

Abstract: The prolactin receptor (PRL-R), a member of the hematopoietin cytokine receptor superfamily, is widely distributed among mammalian tissues. To understand better the potential sites of action and onset of potential PRL responsiveness, the developmental distribution pattern of PRL-R mRNA expression in fetal and neonatal mice was examined. Fetal mouse tissues were collected at distinct stages from timed pregnancies. Following extraction of total RNA, onset of gene expression was evaluated via reverse transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…First appearance of PRL binding was seen in Tc of medium follicles (Bmax = 0.97 ± 0.052, n = 5) , in Tc of large follicle (1.573 ± 0.45, n=7) and in ECL cells (1.7 ±0.14, N=8) which contained the largest number of PRL-R. Discussion PRL binding to ovaries was reported in rat [17,33], hamster [16] mouse [19] and human [20]. Magoffin and Erickson [18,34] demonstrated specific high affinity PRL-Rs in cultured interstitial cells of the rat ovary.…”
Section: Identification Of Prl-r By Binding Assaysmentioning
confidence: 81%
“…First appearance of PRL binding was seen in Tc of medium follicles (Bmax = 0.97 ± 0.052, n = 5) , in Tc of large follicle (1.573 ± 0.45, n=7) and in ECL cells (1.7 ±0.14, N=8) which contained the largest number of PRL-R. Discussion PRL binding to ovaries was reported in rat [17,33], hamster [16] mouse [19] and human [20]. Magoffin and Erickson [18,34] demonstrated specific high affinity PRL-Rs in cultured interstitial cells of the rat ovary.…”
Section: Identification Of Prl-r By Binding Assaysmentioning
confidence: 81%
“…The present study has demonstrated that changes in the ratio of unmodified to phosphorylated PRL in the maternal circulation, produced via administration of recombinant unmodified PRL (U-PRL) or pseudophosphorylated PRL (PP-PRL) have a marked influence on the development of a number of fetal tissues; tissues previously shown by others to express high levels of PRL receptors (Royster et al 1995, Brown-Borg et al 1996, Tzeng & Linzer 1997.…”
Section: Introductionmentioning
confidence: 80%
“…Fetal thymocytes also express the PRL receptor , Royster et al 1995, Brown-Borg et al 1996. In the PP-PRL-exposed pups, the thymus contained abundant apoptotic thymocytes.…”
Section: Figurementioning
confidence: 99%
“…Moreover, PRL receptors have been detected on thymic epithelial cells [8], which may be a direct paracrine target of thymic produced PRL. Recent studies have shown that about 70% of T cells express PRL receptors [3,11,12,14,25]. These findings suggest that PRL may also act as a local cytokine in an autocrine fashion as well.…”
Section: Resultsmentioning
confidence: 95%